2004
DOI: 10.1111/j.1360-0443.2004.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non‐medical drug use and dependence among homosexually active men and women in the US population

Abstract: Aims-The aim of this study was to compare patterns of drug use and dependence between homosexually experienced and exclusively heterosexually experienced individuals.Design-We used a cross-sectional national household interview survey conducted in the United States.Setting-Secondary data analysis of the 1996 National Household Survey on Drug Abuse was employed.Participants-Participants were sexually active individuals, aged 18 years and older, who reported the genders of their sexual partners in the past 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
215
2
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(236 citation statements)
references
References 37 publications
13
215
2
6
Order By: Relevance
“…Prior research has shown high rates of alcohol use among women who partner with women, which may suggest a need for targeted intervention efforts (van Griensven et al, 2004). However, these women did not have higher levels of MA use in contrast to U.S. data showing elevated drug use among homosexually active populations (Cochran et al, 2004). Further research is needed to understand and address substance use patterns among Thai women who partner with women and the influence of their relationship dynamics with family and friends.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prior research has shown high rates of alcohol use among women who partner with women, which may suggest a need for targeted intervention efforts (van Griensven et al, 2004). However, these women did not have higher levels of MA use in contrast to U.S. data showing elevated drug use among homosexually active populations (Cochran et al, 2004). Further research is needed to understand and address substance use patterns among Thai women who partner with women and the influence of their relationship dynamics with family and friends.…”
Section: Discussionmentioning
confidence: 95%
“…Almost 10% of female secondary school students in Bangkok reported "homosexual contact" (O-Prasertsawat & Petchum, 2004) and 8% of female northern Thai students aged 15-21 identified with Thai terms noted as equivalent to 'homosexual' or 'bisexual', with 10% reporting same sex attraction (van Griensven et al, 2004). Although U.S. research shows higher rates of substance use (Cochran, Ackerman, Mays, & Ross, 2004;Scheer et al, 2002) and risk behaviors (Bell, Ompad, & Sherman, 2006;Gonzales et al, 1999) among women who have sex with women, little is known about the drug use and relationship dynamics among Thai women who have female partners.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some studies suggested that almost half of gay and bisexual men (42%-49%) suffer from a psychiatric disorder [10]. In particular, gay and bisexual men appear to suffer from substance use disorders at 2 to 3 times the rate found in the general population [11,12]. Gay as compared with heterosexual men also report lower qualities of life [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…Formerly a favored drug of white, male, blue-collar workers in Hawaii and western United States (US) in the early 1990s (NIDA, 2006), methamphetamine use has become increasingly common among younger adults (Springer et al, 2007) and among gay and bisexual men (Cochran et al, 2004;Thiede et al, 2003).…”
Section: Introductionmentioning
confidence: 99%